Le musiche di scena di Louis Pister per La Tosca di Sardou: edizione critica della partitura (ACME, 2021)
The PhD dissertation of Erin M. Brooks, now Assistant Professor of Music History at the Crane School of Music (State University of New York at Potsdam), investigates the relationship between Sarah Bernhardt, the first performer of Floria in La Tosca, and the music of her time, including incidental music. Within this text, a relevant discovery of the author is mentioned, namely a manuscript of the stage music composed by a certain Louis Pister for Sardou’s pièce, preserved today at the National Library of Australia. The aim of this contribution is to propose a critical edition of the music composed by Pister, an essential document for the analysis of Sardou’s play. Moreover, we will try to reconstruct, through the inspection of contemporary periodicals, the reception of La Tosca and the biographical profile of the forgotten composer of incidental music.